Materialism and compulsive buying behaviour: The role of consumer credit card use and impulse buying. Issue 5 (1st November 2018) - Pradhan, Debasis; Israel, D.; Jena, Amit Kumar
Abstract : Purpose: The purpose of this paper is to study the impact of materialism on credit card (CC) use and impulsive buying (IB) and compulsive buying (CB) behaviour. Furthermore, it assesses whether CC use and IB behaviour mediate the relationship between materialism and CB behaviour. Design/methodology/approach: Data were collected from adult consumers with CCs via an online survey. For model assessment, a two-step approach was followed. First, a measurement model was created and tested using maximum likelihood estimation and validity of the study constructs was assessed. This was followed by structural equation modelling to test the hypotheses. Findings: Materialism influences CC use and increases the propensity for IB (IB), which then precipitates CB habits. Reduction in CC use can decrease both IB and CB. Out of the six hypotheses assessed, only the one linking CC use to CB was not supported, requiring further investigation. Mediation relationships were identified, where CC use and IB act as mediators between materialism and CB. Research limitations/implications: The paper captured responses from adult consumers of India. Hence, the findings may not be generalised across geographies and age groups. The study contributes to the debate on the impulsive–CB paradigm by showing that impulsive and CB are not distinct constructs. In fact, the former could lead to the latter. Practical implications: CC use in itself need not necessarily lead to CB. The only way CC could cause CB is through IB. Hence, firms must promote responsible buying habits, as there has been an increase in IB, which, if not controlled, could lead to debt trap resulting from CB. The findings of this paper will help both retailers and CC institutions to better understand the spending pattern of consumers. Those will also help the policymakers to chalk out ways to the curb indiscriminate issuance of CCs without educating users. Originality/value: The findings confirm that IB and CB exist on two ends of a continuum, and not as two distinct theoretical constructs. IB acts as a mediator between CC use and CB as well as between materialism and CB.